2016
DOI: 10.1001/jamaneurol.2015.4078
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Clinicoradiological Criteria for the Diagnosis of Cerebral Amyloid Angiopathy–Related Inflammation

Abstract: IMPORTANCE Cerebral amyloid angiopathy-related inflammation (CAA-ri) is an important diagnosis to reach in clinical practice because many patients with the disease respond to immunosuppressive therapy. Reliable noninvasive diagnostic criteria for CAA-ri would allow some patients to avoid the risk of brain biopsy. OBJECTIVE To test the sensitivity and specificity of clinical and neuroimaging-based criteria for CAA-ri. DESIGN, SETTING, AND PARTICIPANTS We modified the previously proposed clinicoradiological crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
306
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(323 citation statements)
references
References 24 publications
11
306
0
6
Order By: Relevance
“…107 This hypothesis was recently tested by comparing reconstructed structural brain networks in non-demented patients with probable CAA and aged control participants, where it was found that there was lower global efficiency of the networks in the group with probable CAA, and that this correlated with increased number of CMBs and increased volume of WM ischaemia and infarction. 75 In addition to gradual chronic cognitive decline, patients with CAA can also experience acute stepwise decline in cognitive function after lobar ICH, 30 or may present with a rapidly progressing cognitive decline caused by CAA-ri, 109 which will be discussed later in this review. 75 In addition to gradual chronic cognitive decline, patients with CAA can also experience acute stepwise decline in cognitive function after lobar ICH, 30 or may present with a rapidly progressing cognitive decline caused by CAA-ri, 109 which will be discussed later in this review.…”
Section: Cognitive Impairmentmentioning
confidence: 99%
See 2 more Smart Citations
“…107 This hypothesis was recently tested by comparing reconstructed structural brain networks in non-demented patients with probable CAA and aged control participants, where it was found that there was lower global efficiency of the networks in the group with probable CAA, and that this correlated with increased number of CMBs and increased volume of WM ischaemia and infarction. 75 In addition to gradual chronic cognitive decline, patients with CAA can also experience acute stepwise decline in cognitive function after lobar ICH, 30 or may present with a rapidly progressing cognitive decline caused by CAA-ri, 109 which will be discussed later in this review. 75 In addition to gradual chronic cognitive decline, patients with CAA can also experience acute stepwise decline in cognitive function after lobar ICH, 30 or may present with a rapidly progressing cognitive decline caused by CAA-ri, 109 which will be discussed later in this review.…”
Section: Cognitive Impairmentmentioning
confidence: 99%
“…Histopathologically, it represents a spectrum of disease, ranging from perivascular inflammation consisting of lymphocytes, macrophages and multinucleated giant cells, to an inflammatory process consisting of granuloma formation and inflammation confined to the Abladen vessel wall itself. 109,117 On CT, CAA-ri manifests as asymmetric hypodense subcortical lesions, while on T2 FLAIR MRI, these lesions have high signal and involve the subcortical U fibres, 33,119 as appreciable in Figure 7. [116][117][118] Clinically, CAA-ri can present with subacute or rapidly progressive cognitive decline, headache, hallucinations, focal neurological signs, focal seizures or decreased consciousness.…”
Section: Cerebral Amyloid Angiopathy-related Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, idiopathic CAA-related inflammation is a rare disorder [36, 37] that manifests in various ways [38] and has been given a number of monikers, such as Aβ-related angiitis (ABRA), cerebral amyloid inflammatory vasculopathy, and others [39]. CAA-related inflammation in humans involves the incursion of inflammatory cells [36], and in many (but not all) cases, CAA-related inflammation responds favorably to immunosuppressive agents [36, 39, 40]. The extent to which the cellular inflammatory reaction per se contributes to the aberrant MRI signal hyperintensities in T2-weighted scans (as opposed to the contribution of vasogenic edema alone) is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is the elevated predisposition of older African-Americans to lobar hemorrhage[25], a disorder that has been linked to cerebral amyloid angiopathy (CAA)[26, 27]. Neuropathologically, CAA is characterized by the deposition of amyloid in and around the walls of cerebral blood vessels[2830].…”
Section: Introductionmentioning
confidence: 99%